The last voyage of Capt. Sir John Ross, R.N. Knt. to the Arctic regions [electronic resource] : for the discovery of a north west passage; performed in the years 1829-30-31-32 and 33 : to which is prefixed an abridgement of the former voyages of Captns. Ross, Parry, & other celebrated navigators to the northern latitudes : compiled from authentic information and original documents, transmitted by William Light, purser' s steward to the expedition : illustrated by engravings from drawings taken on the spot - Huish, Robert, 1777-1850. (Saint John, N.B. : [s.n., 1868)
This unauthorized account of the expedition was designed, as stated by Huish, as a popular priced substitute for Ross' official publication--Cf. Introd. Tables. Added t.p., engraved. "Printed for the Proprietors . and sold by all Booksellers in the United Kingdom." Electronic reproduction. Mode of access: Internet. 44